EFEKTIVITAS PROGRAM BKP KAMPUS MERDEKA PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSTIAS NEGERI MAKASSAR - Rahmat, Abdul; Piara, Muhrajan (Jurnal Al-Fatih, 2024)
This study aimed to evaluate the program of Bentuk Kegiatan Pembelajaran (BKP) which is an initiation of the policy called Kampus Merdeka from Indonesian Ministry of Education, Culture, Research, and Technology. This study measured the effectiveness of BKP program which has been implemented by collage students at several institutions around Makassar. The participants in this research were 43 students consisted of 9 males and 34 females. Data collection was carried out by distributing questionnaires via Google Form to participants and then analyzed using descriptive statistical techniques. The result of this study showed that the majority of participants considered that the BKP program was running well, although there were still several lacks, such as activities during BKP which were considered boring, learning methods that were unable to explore students' abilities, and a mismatch between student expectations and the real condition of BKP program. It is hoped that the results of this study can be used as a consideration for lecturers who guide students in the next program to provide a more detailed understanding to students and partners.